Strategi Kepala Sekolah dalam Mempengaruhi Employe Engagement terhadap Kinerja Pendidik di SMP Muhamadiyah 10 Surakarta - Shema Andi Prasetya; Istanto Istanto (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Schools play a central role in the process of educating the nation's children. In education, the figure of the educator determines the progress of the school. So, the role of educational organizations is very large in the development process. The school organization must have a strategy to maintain the quality of educators to remain ideal, because the quality climate of educators greatly impacts students. This study aims to identify and analyze the principal's leadership strategy in improving employee engagement on educators' performance at SMP Muhamadiyah 10 Surakarta. The method used with descriptive method using qualitative approach. Data collection used interview, documentation and observation methods. Testing the validity of data using triangulation. Data analysis used through data reduction, data presentation, conclusion drawing. The results showed that employee engagement at SMP Muhammadiyah 10 Surakarta has been well realized through the principal's strategy and the application of ethical values to educators to encourage the development of educators. The strategies/programs that have been implemented are: 1). Strengthening class leadership, 2). Maintenance of commitment through relationship development, 3). Teacher involvement in decision making, 4). Improved communication, 5). Reward and recognition, 6). Positive work culture. Future research can expand the study on the development of the principal's leadership model on student learning outcomes and evaluate the effectiveness of the principal's strategy that has been implemented.